EVALUATION OF THE CAUSES AND SOCIO-ECONOMIC IMPACTS OF ERO RIVER FLOODING IN MOBA LOCAL GOVERNMENT AREA, EKITI STATE, NIGERIA - Ekiran, Ekiran; Joseph Ojo (Bajang Institute, 2023)
Flood is a local and global environmental menace. It is worrisome to note that river flood disasters have become an annual endemic problem in many parts of Ekiti State especially on Ero river which ususally affect the residents of Moba local government area of the state. There are many studies on the causes and effects of flood in Nigeria. Studies on recent impact of river flood disaster on socio-economic activities of the people in Ekiti State are very scarce in literature. This research work therefore aims at evaluating the causes and socio-economic impact of Ero river flooding in Moba local government area, Ekiti State, Nigeria. The study uses ex-post factor quantitative research design, employs 4-point Likert-type scaling instrument and applies descriptive statistics method of data analysis. The results confirmed loss of human lives, damage of valuable properties, and socio-economic hazards faced by the victims of Ero river flood. The research work recommends effective waste management board, construction and maintenance of deep and wide drainage systems, and compliance with the rules and regulations of the monthly environmental sanitation programme in the process of flood control in Moba local government area, Ekiti State, Nigeria